1999
DOI: 10.1016/s0960-9822(99)80238-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the tyrosine phosphatase PTPα leads to constitutive downregulation of the kinases Src and Fyn

Abstract: A role for the receptor-like protein tyrosine phosphatase alpha (PTPalpha) in regulating the kinase activity of Src family members has been proposed because ectopic expression of PTPalpha enhances the dephosphorylation and activation of Src and Fyn [1] [2] [3]. We have generated mice lacking catalytically active PTPalpha to address the question of whether PTPalpha is a physiological activator of Src and Fyn, and to investigate its other potential functions in the context of the whole animal. Mice homozygous fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
191
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(202 citation statements)
references
References 15 publications
11
191
0
Order By: Relevance
“…Our group and others showed that Src and Fyn are activated by RPTP␣-mediated dephosphorylation both in fibroblasts (Ponniah et al, 1999;Su et al, 1999;von Wichert et al, 2003) and neurons (Bodrikov et al, 2005;Helmke et al, 1998;Zeng et al, 1999).…”
Section: Introductionmentioning
confidence: 84%
“…Our group and others showed that Src and Fyn are activated by RPTP␣-mediated dephosphorylation both in fibroblasts (Ponniah et al, 1999;Su et al, 1999;von Wichert et al, 2003) and neurons (Bodrikov et al, 2005;Helmke et al, 1998;Zeng et al, 1999).…”
Section: Introductionmentioning
confidence: 84%
“…The most likely tyrosine phosphatase involved in response to cell adhesion is the transmembrane phosphatase PTPa . Downregulation of Src and Fyn kinases has been observed in ptpaÀ/À cells, which correlated with enhanced tyrosine phosphorylation of the negative regulatory element (Ponniah et al, 1999). These fibroblasts lacking PTPa also exhibit defective tyrosine phosphorylation of substrates for cell adhesion-induced tyrosine phosphorylation (Ponniah et al, 1999;Su et al, 1999;Zeng et al, 2003).…”
Section: Dephosphorylation Of Src Y527mentioning
confidence: 95%
“…Third, RPTPa is an important regulator of SFK activity, by controlling dephosphorylation of the carboxy-terminal negative regulatory Y530 site of cSrc. Cells lacking RPTPa display reduced Fyn and cSrc kinase activities, and exhibit defects similar to those resulting from lack of c-Src (Ponniah et al, 1999;Su et al, 1999). Conversely, RPTPa overexpression results in elevated c-Src kinase activity (den Hertog et al, 1993;Zheng et al, 1992Zheng et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%